Intervensi pencegahan kekerasan seksual pada remaja: Literature review - Tetti Solehati; Asep Solahudin; Risma Juniarti; Siti Fauziah; Rizki Romadona; Riska Audina; Sely Novianty; Riki Kurniawan; Cecep Eli Kosasih (Holistik Jurnal Kesehatan, 2023)
Background: Sexual abuse in adolescents is a worrying problem, and has a serious physical, mental, and psychological impact on the victims.Purpose: To analyze effective interventions in preventing sexual violence in adolescents.Method: This literature review used the Preferred Reporting Items for Systematic Reviews (PRISMA) guide with the keywords “Intervention” AND “sexual violence” AND “prevention” AND “youth” using the Science Direct, PubMed, Medline, ProQuest, and Sage Journal databases. The inclusion criteria included full text, in English, and the year of publication ranged from 2010 to 2020. 23,517 articles were collected according to keywords and 9 articles were selected that met the quality requirements.Results: Based on the literature review, there were 5 intervention groups including interventions using school-based sexual education curricula, media games and educational games, mixed interventions, support groups, and workshops which proved effective in preventing sexual violence in adolescents.Conclusion: Various interventions have been found to be effective so that they can be used as a youth sexual violence prevention program. In research, it is rare to find the involvement of nurses and families in carrying out interventions.Suggestion: The findings of this study can be input for further research related to the prevention of sexual violence in adolescents by involving the role of the family and the role of nurses. This study can be a reference for policymakers in determining preventive actions that can be taken to reduce sexual violence in adolescents.Keywords: Adolescents; Intervention; Literature Review; Prevention; Sexual AbusePendahuluan: Kekerasan seksual pada remaja menjadi permasalahan yang mengkhawatirkan, berdampak serius pada fisik, mental dan psikologis pada korbannya.Tujuan: Untuk menganalisa intervensi yang efektif dalam pencegahan kekerasan seksual pada remaja.Metode: Literature review ini menggunakan panduaan Preferred Reporting Items for Systematic Reviews (PRISMA) dengan kata kunci “Intervensi” AND “kekerasan seksual” AND “pencegahan” AND “remaja” dengan menggunakan database Science Direct, PubMed, Medline, ProQuest, dan Sage Journal. Kriteria inkluasi meliputi fulltext, berbahasa inggris, dan rentang tahun publikasi antara 2010 sampai 2020. Terkumpul 23.517 artikel sesuai dengan kata kunci dan terpilih 9 artikel yang memenuhi syarat kualitas.Hasil: Berdasarkan literature review terdapat 5 kelompok intervensi diantaranya, intervensi menggunakan kurikulum pendidikan seksual berbasis sekolah, pemanfaatan media permainan dan game edukasi, intervensi campuran, support group, dan lokakarya yang terbukti efektif dalam mencegah kekerasan seksual pada remaja.Simpulan: Berbagai intervensi yang ditemukan efektif sehingga dapat digunakan menjadi program pencegahan kekerasan seksual remaja. Pada penelitian jarang ditemukan keterlibatan perawat dan keluarga dalam melakukan intervensi.Saran: Temuan studi ini dapat menjadi masukan untuk penelitian selanjutnya terkait pencegahan kekerasa seksual pada remaja dengan melibatkan peran keluarga dan peran perawat. Studi ini dapat menjadi rujukan bagi pemegang kebijakan dalam menentukan tindakan pencegahan yang dapat dilakukan untuk menurunkan kekrasan seksual pada remaja.